Ultimele cuvinte… - Dan Sluşanschi; Lucia Toader (Revista de Istorie și Teorie Literară)
The last inteview (January 2008, Radio Trinitas) with professor Dan Sluşanschi (1943–2008), a remarkable translator from Medieval Greek and Latin revealed some unknown aspects of translating. Dan Sluşanschi talked about the beauty of Cantemir’s language (he translated many of Cantemir’s books) and he pointed to the gaps in the Romanian higher education system.